Protection for intangible cultural heritage as a viable tourist product: Malaysia as a case study - Nublan Zaky, Sharafina Zaky; Abdul Ghani Azmi, Ida Madieha (The Malaysian Consumer and Family Economics Association, 2017)
The realization of the importance of intangible cultural heritage (ICH) has led governments around the world to protect these resources in order to promote tourism. Malaysia, in this respect, is not exceptional. Having ratified the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage in 2013, Malaysia is bound to identify and define the various elements of the ICH present in its territory and ensure its protection. It is the purpose of this article to discuss the protection available for ICH that could be further developed to attract tourists. In particular, the article seeks to examine the UNIESCO Convention for the Safeguarding of the Intangible Cultural Heritage and the existing heritage laws in Malaysia. The existing laws refer to the National Heritage Act 2005 as well as the States' heritage enactments that provide for the preservation of cultural heritage resources at both federal and state levels. The problems to be addressed include, inter alia, lack of proper understanding on the nature of ICH and the narrow interpretations and scope of ICH. This article concludes with some recommendations for legislative reform to better protect ICH and ensure the rapid development of tourism in Malaysia